Next Industrial Relations Conferences in Canadian Universities

(untitled) (Département des relations industrielles de l'Université Laval, 1965)
In the following months, two Industrial Relations Centers of Canadian Universities will hold their Industrial Relations Conference. At McGill University, September 9th and 10th, will be studied the problem of Canadian autonomy in Labour-Management Relations under the title of DOMINATION OR INDEPENDANCE? The Center of the University of Toronto is organizing its founding Conference, October 13-15. The subject is INDUSTRIAL RELATIONS IN THE NEXT DECADE: CHALLENGES AND RESPONSES. Here are the programs.